2002
DOI: 10.1016/s0896-6273(02)01061-9
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Negative BOLD, Blood Flow and Oxygen Consumption Response and Its Coupling to the Positive Response in the Human Brain

Abstract: Most fMRI studies are based on the detection of a positive BOLD response (PBR). Here, we demonstrate and characterize a robust sustained negative BOLD response (NBR) in the human occipital cortex, triggered by stimulating part of the visual field. The NBR was spatially adjacent to but segregated from the PBR. It depended on the stimulus and thus on the pattern of neuronal activity. The time courses of the NBR and PBR were similar, and their amplitudes covaried both with increasing stimulus duration and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
446
8
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(511 citation statements)
references
References 49 publications
52
446
8
5
Order By: Relevance
“…The deactivation found in our experiment could therefore be caused by such an attention demand (i.e. 'vascular steal'; [49]) resulting from observing the video sequences on screen.…”
Section: Discussionmentioning
confidence: 74%
“…The deactivation found in our experiment could therefore be caused by such an attention demand (i.e. 'vascular steal'; [49]) resulting from observing the video sequences on screen.…”
Section: Discussionmentioning
confidence: 74%
“…A specific aspect of BOLD contrast where there is continuing controversy on the interpretation of fMRI data is the existence of negative BOLD and its link with neural activity Shmuel et al, 2002;Devor et al, 2007;Northoff et al, 2007;Schridde et al, 2008;Woolsey et al, 1996). In the first paper of this series, Woolsey et al (1996) studied the links between neuronal units and micro-vascular modules in cerebral cortex of the rodent whiskerbarrel system.…”
Section: Hemodynamic Variations Induced By Local Vasodilationsmentioning
confidence: 99%
“…Recent studies have provided evidence of a neural component to the inhibitory rebound. Shmuel et al (2006Shmuel et al ( , 2002 have studied the origin of the negative BOLD activation in cortical regions adjacent to those receiving direct projections from stimulated retina and shown that it cannot be attributed to blood dynamics but must be a result of a reduction in the neuronal signal in those regions. Such studies imply that it is reasonable to attribute negative BOLD signals to inhibitory suppression of neural activity, especially in the present situation when (1) there is no diVerence in the local stimulation between the test-and the null-epochs, (2) and the only sites of activation are remote from the zone of reduced BOLD response.…”
Section: Analysis: a Recurrent Wgure/ground Modelmentioning
confidence: 99%